E-LKPD Berbasis Problem Based Learning Disertai Kuis Interaktif Matematika untuk Meningkatkan Kemampuan Berpikir Kritis - Risa Dewi Munika; Retno Marsitin; Nyamik Rahayu Sesanti (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
This development research aims to determine the process of developing E-LKPD (Electronic Student Worksheets) based on Problem Based Learning accompanied by interactive math quizzes to improve students' critical thinking skills that are valid, feasible and effective. The results of observations of mathematics learning in class X MIPA at SMAN 1 Malang show that there are no teaching materials that use interactive live worksheets. Critical thinking is the ability to solve problems which include steps to identify, organize and implement strategies and techniques, evaluate and draw conclusions. This type of research is the development of the ADDIE model (Analysis, Design, Development, Implementation, Evaluations). The research results from the validity test have an average of 3.33 by design experts with a very valid category, 3.27 by mathematics learning experts with a very valid category and 3.11 by material experts with a valid category. The results of the feasibility test on a small scale obtained a percentage of 81% with a very feasible category and 86% on a large scale trial with a very feasible category. The results of the effectiveness test obtained a percentage of completeness 100% in small-scale trials and 86% in large-scale trials so that both obtained effective categories. The conclusion of this study is that E-LKPD based on Problem Based Learning with interactive math quizzes is valid, feasible and effective and can improve students' critical thinking skills.